2020
DOI: 10.1016/j.memsci.2020.118066
|View full text |Cite
|
Sign up to set email alerts
|

Binaphthalene-based polymer membranes with enhanced performance for solvent-resistant nanofiltration

Abstract: To improve the performance of the currently available solvent-resistant nanofiltration (SRNF) membranes, a new, unique approach was developed. In this approach, the concept of PIMs is combined with the fabrication of thin film composite membranes by interfacial polymerization (IFP) ànd the possibility to tune the molecular structure of the monomers at wish. This allows to obtain a thin active layer with a high free volume and good permeance for solvents while realizing a high solute retention. The influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
(82 reference statements)
0
26
0
Order By: Relevance
“…The selected amine monomers are shown in Fig. 1, with a the amine monomer with the highest number of amine functionalities and the lowest reactivity in the used set-up [14]. As shown in previous work, not only the number and position of the amine functionalities matter, but also their reactivity during IP is key.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The selected amine monomers are shown in Fig. 1, with a the amine monomer with the highest number of amine functionalities and the lowest reactivity in the used set-up [14]. As shown in previous work, not only the number and position of the amine functionalities matter, but also their reactivity during IP is key.…”
Section: Introductionmentioning
confidence: 95%
“…A methyl-linked binaphthalene di(acid chloride) was specifically chosen (Fig. 1), since previous findings showed that a smaller dihedral angle, obtained by using a short linker, gives better results for SRNF [14]. Most importantly, since binaphthalenes are chiral, the enantiomeric excess of the monomer can be varied and its influence on the structure and thus the membrane performance can be studied.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a higher selectivity, improved chemical, and thermal stability could be achieved. The most commonly used polymer is PI, including P84 [ 16,20,22,23,46,49–55 ] and matrimid [ 56–61 ] PI. After covalent crosslinking by diamines (e.g., 1,6‐diaminohexane) in an alcoholic solvent (isopropanol (IPA) or methanol), the resultant cross‐linked PI‐based TFC membrane could be tolerant to a wide range of mild organic solvents as well as a harsh polar aprotic solvent (DMF).…”
Section: Substrate Layermentioning
confidence: 99%
“…Additional precautions are necessary to prevent degradation of the free amines when applying the IP reaction; for instance, Ar gas is required to purge into the aqueous solution and the IP set‐up also has to be continuously provided with inert gas. [ 59 ] To achieve a higher solvent permeability but maintain the selectivity of a TFC membrane, amines with non‐planer structure could be used as an additive to enhance the free volume in the selective layer. [ 90 ] Additionally, heterocyclic compounds and aliphatic amines could also be potentially used as the aqueous monomers in the IP reaction due to their chemical stability, lower toxicity, and water solubility.…”
Section: New Monomers For Interfacial Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation